MicroRNA Expression and Neurocognitive Outcomes in Children and Young People With Primary Brain Tumor in Karachi, Pakistan: A Pilot Exploratory Study - Zahid, Nida; Mughal, Muhammad Nouman; Brown, Nick; Mårtensson, Andreas; Mårtensson, Thomas; Ibrahim, Muhammad Sufiyan; Naeem, Sana; Qazi, Siraj; Amin, Wajiha; Azam, Iqbal; Mushtaq, Naureen; Moochhala, Mariya; et al. (Brain tumor research and treatment, 2025)
microRNAs regulate various cellular pathways and may serve as medium-term prognostic markers in neurocognitive function, as suggested by adult studies. However, no comparable data exist for children with central nervous system tumors. This pilot study explored miRNA expression and its correlation with 12-month posttreatment neurocognitive function in children and young adults (5-21 years) with primary brain tumors. The study was conducted at Aga Khan University Hospital and Jinnah Postgraduate Medical Center (November 2020 to July 2023). This study analyzed serum levels of miR-21, miR-146a, miR-296-5p, miR-210, and miR-10b using reverse transcriptase quantitative PCR. Neurocognitive assessments using Slosson Intelligence Test, Raven's Progressive Matrices, and Wechsler Intelligence Scale were performed at pretreatment and 12 months posttreatment. The paired t-test was used to assess miRNA expressions, and correlation analysis assessed relationships between pretreatment miRNA expression and neurocognitive outcomes. Of the 48 patients, serum samples were available for analysis from 34 (71%) patients each at pretreatment and 48 hours post-surgery, and 13 (27%) patients at 12 months posttreatment. A statistically significant negative correlation was found between pretreatment miR-210 levels and perceptual reasoning scores at 12 months posttreatment (ρ=-0.59), and a positive correlation between pretreatment miR-10b levels and processing speed scores (ρ=0.49). However, there were no differences in microRNA expressions between pretreatment and 48 hours post-surgery (n=34), pretreatment and 12 months posttreatment (n=13), or 48 hours post-surgery and 12 months posttreatment. This pilot exploratory study found two statistically significant correlations: a negative correlation between pretreatment miR-210 levels and 12 months posttreatment perceptual reasoning scores and a positive correlation between miR-10b expression and 12 months posttreatment speed scores. Further studies are needed to understand the protective or restorative function of miR-10b in cognitive processes and the detrimental role of miR-210 in cognitive processes to evaluate their potential future use as prognostic biomarkers for neurocognitive outcomes in children and young people with primary brain tumors.